Augmented Reality for assembly operation training: does immersion affect the recall performance? - Generosi, Andrea; Agostinelli, Thomas; Mengoni, Maura; Ceccacci, Silvia (2022 IEEE International Conference on Metrology for Extended Reality, Artificial Intelligence and Neural Engineering (MetroXRAINE), 2022)
This study aims at comparing three assembly training applications based on different XR technologies characterized by different degrees of immersion (i.e., an MR application based on Hololens 2, a desktop AR application and a digital handbook visualized on a monitor). A total of 54 subjects, recruited among students and personnel of Università Politecnica delle Marche, have been involved. They were assigned to 3 groups age and gender matching. Each group is asked to complete the training related to the assembly of a Lego commercial set (i.e., LEGO 10593), using one of the three considered applications. Results allows us to observe the effects of the immersion on the recall performances, assessed in terms of recall completion time, assembly mistakes, picking mistakes and sequence mistakes.